Investigation in to Energy Storage of Solar Energy Harvesting Wireless Sensor Network - Ali Ahmed, Hassan Abdelrahman (Universiti Teknologi PETRONAS, 2016)
Solar Energy Harvesting Wireless sensor networks (SEH-WSNs) have enabled a wide variety of applications that require low cost, low power, remote monitoring due to their ease of deployment coupled with their ability to operate perpetually. However solar photovoltaic cells do not produce a consistent energy output throughout the day due to shadowing and varying sunlight intensity therefore the presence of a high capacity storage solution as well as an energy buffer is vital for continuous operation.